Company Relocation: The Consequences for Employees - An Analysis of the WSI Works Council Survey - Elke Ahlers; Fikret Oez; Astrid Ziegler (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2007)
This study, based on the 2005 WSI Works Council Survey, aims to highlight the ramifications of company relocations on employees as well as the role of company relocation in the work of the works councils. The study is rounded off with an analysis of the policy framework, which looks at how policy has reacted to the public debate on company relocations. Concluding comments complete the study.
Keywords: 330; Industrieverlagerung; Auslandsproduktion; Mitbestimmung; Beschäftigungseffekt; Arbeitsbedingungen; Deutschland